Impact of Agro-Chemicals on Groundwater Quality and Soils of Irrigation Sites: A Case Study of Chanchaga Irrigation Scheme, Minna, Niger State - Mohammed B. ABDULLAHI (FUDMA Journal of Engineering and Technology, 2026)
The research work was conducted at the Chanchaga irrigation scheme aimed to identify the often-used agrochemicals by farmers and their impact on soil and groundwater in the scheme. Groundwater and soil samples were collected from the scheme and analysed for K, Cl, NO3, and PO4 using flame photometer and Ultra-Violet (UV) Spectrophotometer, for the heavy metals (Mn, Zn and Cr) Atomic Absorption Spectrophotometer (AAS) was used. For the survey analysis, a well-structured questionnaire and data from the municipal agriculture office were used in the data collection. A total of 113 respondents (farmers) were surveyed, most of the farmers (88.97%) were using agrochemicals and inorganic fertilisers. Correlation and ANOVA analysis were used to analyse the data. The results showed high occurrence of NO3, PO4, Mn, Zn and Cr in both samples. And were statistically observed to be significantly different at p≤0.05 in the soil and groundwater of the Scheme. Farmers indiscriminately used agrochemicals without consideration to dosage and rate of application. Insignificant number of the farmers applied biological control methods for crop pests and diseases. Therefore, increasing the awareness and training of farmers in sustainable agriculture and agrochemical use, within an integrated pest management approach is necessary and recommended.
Keywords: Agrochemicals, groundwater contamination, and soil contamination.